HIGH SERUM CONCENTRATION OF INTERLEUKINE-6 AND RANK-LIGAND AS RISK FACTORS FOR OSTEOPOROSIS IN ESTROGEN DEFICIENCY POST-MENOPAUSAL WOMEN - Siki Kawiyana, Ketut; Surya, Gusti Putu; Bakta, Made; Roeshadi, Djoko (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Osteoporosis in post-menopausal women is not merely due to deficient estrogenhormone production. The development of osteoporosis is due to increased boneresorption by osteoclasts. The osteoclast’s number and activity is controlled by activatingfactors such as IL-6 and RANK-L. The objective of this study was to determine that highIL-6 and RANK-L serum concentrations are risks for osteoporosis in estrogen deficientpost-menopausal women. The serum concentration of ß-CrossLaps (CTx) was measuredto determine bone resorption rate. This is an observational analytical study using case andcontrol design conducted at Sanglah General Hospital of Denpasar. The sample size wascalculated using the paired case-control study formula. There were 41 osteoporotic and41 non-osteoporotic (control) estrogen deficient post-menopausal women involved in thestudy.Data were analyzed by using the t-paired and McNemar tests. Mean serumconcentration of IL-6 among the osteoporotic women was significantly higher ascompared to that of the controls (3.47±1.75 pg/ml vs 2.51±1.13 pg/ml, p = 0.001). Meanserum concentration of RANK-L among the osteoporotic women was also significantlyhigher as compared to that of the controls (320.66±122.44ng/ml vs 249.94±82.41 ng/ml,p = 0.002). To qualify as risk factors for osteoporosis, the cut-off point for IL-6 was 2.17pg/ml (OR = 4, CI 95%: 1.23-14.24; p = 0.032); the cut-off point for RANK-L was275.165 ng/ml (OR = 8, CI 95%: 1.84-34.79; p = 0.001). Analysis of both high serumconcentration of IL-6 and RANK-L was associated with an odd ratio of 9 (CI 95%: 4,27-18,96, p=0,000). CTx concentration in the osteoporotic women was significantly higherthan in the controls (0.60±0.22ng/ml vs 0.46±0.16ng/ml, p = 0.004).We found that the high IL-6 and RANK-L serum concentrations were risk factorsin estrogen deficient post-menopausal women. CTx being a marker for osteoclastic boneresorption activity, increased in concentration higher in osteoporotic than in nonosteoporoticwomen. The high serum concentrations of IL-6 and RANK-L could be usedas predictors for osteoporosis in estrogen deficient post-menopausal women.
Keywords: Post-menopausal osteoporosis, estrogen, osteoclast activity, ß-Cross, (CTx), Interleukine-6, RANK-Ligand